Recommended Dietary Pattern to Achieve Adherence to the American Heart Association/American College of Cardiology (AHA/ACC) Guidelines: A Scientific Statement From the American Heart Association - Van Horn, Linda; Carson, Jo Ann S; Appel, Lawrence J; Burke, Lora E; Economos, Christina; Karmally, Wahida; Lancaster, Kristie; Lichtenstein, Alice H; Johnson, Rachel K; Thomas, Randal J; Vos, Miriam; Wylie-Rosett, Judith; et al. (Circulation (New York, N.Y.), 2016)
In 2013, the American Heart Association and American College of Cardiology published the "Guideline on Lifestyle Management to Reduce Cardiovascular Risk," which was based on a systematic review originally initiated by the National Heart, Lung, and Blood Institute. The guideline supports the American Heart Association's 2020 Strategic Impact Goals for cardiovascular health promotion and disease reduction by providing more specific details for adopting evidence-based diet and lifestyle behaviors to achieve those goals. In addition, the 2015-2020 Dietary Guidelines for Americans issued updated evidence relevant to reducing cardiovascular risk and provided additional recommendations for adopting healthy diet and lifestyle approaches. This scientific statement, intended for healthcare providers, summarizes relevant scientific and translational evidence and offers practical tips, tools, and dietary approaches to help patients/clients adapt these guidelines according to their sociocultural, economic, and taste preferences.